Development of a self-assessment/benchmarking tool for regulators of veterinary medicines - Joseph, Noel; Borriello, S. Peter; Eckford, Suzanne; Oyati, Osi (Frontiers in Veterinary Science, 2025)
The regulation of veterinary medicines is important for animal health and welfare, for human health, for sustainable food production, and for minimising impacts on the environment. The capability to regulate these medicines is therefore also important to provide confidence to stakeholders, particularly the public. Although there is a Global Benchmarking Tool to assess the capability of regulatory bodies for human medicines, developed by the World Health Organisation (WHO), the veterinary regulatory sector lacks a similar global, comprehensive scheme and associated guidance. A review of schemes that address veterinary medicines regulatory bodies was undertaken and compared to the WHO scheme to develop a proposed scheme for regulators of veterinary medicines. This new tool will provide a comprehensive and systematic approach to strengthening regulatory systems, fostering harmonisation, and ensuring the quality, safety, and efficacy of veterinary medicinal products.